Adrenal Insufficiency (BIRDEM Medical Journal, 2016)
Adrenal insufficiency means hypo-function of the adrenal cortex, usually glucocorticoid, may be associated with mineralocorticoid and rarely adrenal androgen. It can be categorized into two types: Primary adrenal insufficiency, or Addisons disease (cortisol low and ACTH high) or secondary/ tertiary adrenal insufficiency due to pituitary or hypothalamic disorders (both cortisol and ACTH are low). Identification of etiology is very important for plan of treatment. The reported incidence of adrenal insufficiency varies greatly depending on the population studied, the test and cut off levels used, and the cause. Many patients may present with adrenal crisis, some of them have subtle symptoms, hyperpigmentation, hypotension, electrolyte imbalance, shock etc. Many of them have iatrogenic adrenal insufficiency with features of Cushings syndrome. So, the manifestations of adrenal insufficiency are numerous and nonspecific, and clinicians should have a high index of suspicion and be alert to see important diagnostic clues, such as hyponatremia, hyperkalemia, and hypotension (that are refractory to fluids and vasopressors), diarrhea, weight loss, vomiting, fever etc. without any clear causation. Treatment of adrenal insufficiency is usually life-long, of course based on etiology. Short acting glucocorticoid is better, like hydrocortisone. Patients may be treated with prednisolone. Patients should be provided a steroid card. Sometimes it is essential to take patients under withdrawal protocol.Birdem Med J 2015; 5(1) Supplement: 43-48